Robust 2DOF fuzzy gain scheduling control for DC servo speed controller - Chitsanga, Natchanon; Kaitwanidvilai, Somyot (My University, 2016)
This paper proposes a new design method called “robust 2DOF fuzzy gain scheduling control” for a DC servo speed control system. The proposed technique utilizes the basic concept of 2DOF robust loop shaping, whose time-domain specifications are combined during the controller design using a reference model. In addition, the local controllers are fixed- structure robust controllers whose structure can be specified as for a simple controller. A fuzzy approach is adopted in both system identification process and global control structure to accomplish an entirely robust system. Although the design of robust control in a fuzzy system is not easy, genetic algorithms (GAs) simplify the control design problem to design the fuzzy controller such that the average stability margin is minimized. Implementation of a DC servo speed control was adopted to investigate the effectiveness of the proposed controller. As seen from the results, the proposed controller has more robust performance and can be adopted in applications with a wide operating range. © 2016 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.
Keywords: 2DOF H-infinity control; DC servo system; fixed-structure fuzzy gain; genetic algorithm; scheduled controller; T–S fuzzy system identification